Hyperbaric oxygen therapy for chronic radiotherapy‐related adverse effects: A clinically focused review - Cas Stefaan Dejonckheere; Lukas Käsmann; Leonard Christopher Schmeel; Stefanie Walter; Teresa Anzböck; Sven Dreyer; Gustavo Renato Sarria; Eleni Gkika; Julian Philipp Layer (CA: A Cancer Journal for Clinicians, 2026)
Abstract Radiotherapy is a cornerstone of modern oncologic care, yet its sequelae can significantly impair survivors' quality of life. Chronic radiation‐induced conditions—including skin fibrosis, bone necrosis, radiation cystitis, and proctitis—pose substantial challenges for both patients and caregivers, particularly in the context of improving long‐term cancer survival. Hyperbaric oxygen therapy, characterized by the promotion of angiogenesis, fibroblast activation, and tissue remodeling in hypoxic environments, has emerged as a potential adjunctive treatment for mitigating these late effects. Herein, the authors critically evaluate randomized trials, cohort studies, and real‐world data while highlighting gaps in knowledge, including patient selection, optimal treatment protocols, and long‐term outcomes. In addition, they discuss practical considerations and health system implications of the integration of hyperbaric oxygen therapy into survivorship care. The objective of this review is to provide clinicians with an evidence‐informed framework to guide decision making in the multidisciplinary management of radiation‐related late effects.